Biomass Production, Phosphorus and Nitrogen Content in Acacia Nilotica under Am Fungi and Nutrient Treated Soil - Singh, Kaushal Pratap; Yadav, Rekha; Kumari, Preetesh; Bhadauria, Seema (Indian Forester, 2014)
Acacia nilotica is fast growing, drought resistant, multipurpose legume tree species occurring in semi-arid and arid zones of the world. AM fungi, which constitute a group of important soil microorganisms, are known to improve the plant growth through better uptake of nutrients. A total of eight sets of experiments were conducted to analyze maximum biomass accumulation, phosphorus and nitrogen content in Acacia nilotica. The results of present investigation showed the maximum biomass accumulation, phosphorus and nitrogen content were achieved under soil treated with AM along with phosphate and nitrogenous fertilizers. In another set of experiment, the increased biomass accumulation, phosphorus and nitrogen content in Acacia nilotica were found under soil treated with AM along with phosphate fertilizer followed by soil treated with AM along with nitrogen fertilizer. It was comparatively lowerin soil treated only with AM fungi.